Diversity and distribution of epiphytic lichens on Cedrus atlantica and Quercus faginea in Mount Babor Forest, Algeria - Amina Belguidoum; Takia Lograda; Messaoud Ramdani (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Belguidoum A, Lograda T, Ramdani M. 2021. Diversity and distribution of epiphytic lichens on Cedrus atlantica and Quercus faginea in Mount Babor Forest, Algeria. Biodiversitas 22: 887-899. Information about lichen diversity in Algeria is limited despite their important role as biological indicators of ecosystem health. The aim of the study was to carry out an inventory of epiphytic lichens in the Mount Babor Forest on two types of phorophytes (host trees), i.e., Cedrus atlantica and Quercus faginea, in varying altitudinal gradients and the diameter of host tree. The similarity of the sampled sites was assessed by the Sorensen index (?). Sixty-six species of epiphytic lichens were identified, which belong to 24 families and 38 genera. C. atlantica hosted a higher number of species than Q. faginea. The majority of lichen on C. atlantica belonged to the Parmeliaceae family, whereas those on Q. faginea belonged to the Physciaceae family. Crustose and foliose lichens were the most common species in the study area. The results showed the existence of a distinct relationship between the parameters of the distribution (i.e., tree diameter, elevation) and the specific lichen richness. The greatest number of lichen species (59 species) was observed on large diameter trunks (41-60 cm). Lichen diversity increased along with the increase in altitude. Sorensen’s similarity index revealed the presence of heterogeneity in the community composition of lichen vegetation.